The influence of work motivation and discipline on employee performance with leadership style as a moderating variable - Faryani, Meri; Utomo, Kabul Wahyu; Sultan, Zulkifli (Institute of Computer Science (IOCS), 2024)
This study examined the influence of work motivation and discipline on employee performance, with leadership style as a moderating variable. Conducted among employees of the Dinas Pemberdayaan Masyarakat dan Desa Kabupaten Simeulue, the research employed a mixed-methods approach, integrating quantitative and qualitative data. The quantitative phase involved a survey of 150 employees, revealing that work motivation (? = 0.50, p < 0.001) and work discipline (? = 0.40, p < 0.001) significantly impacted employee performance. Hierarchical multiple regression analysis demonstrated that leadership style significantly moderated these effects, enhancing the positive impacts of motivation (Interaction ? = 0.25, p < 0.01) and discipline (Interaction ? = 0.20, p < 0.01) on performance. Qualitative interviews further supported these findings, indicating that supportive and culturally sensitive leadership boosted employee morale and performance. The results suggested that fostering a motivated and disciplined workforce through targeted HR practices and leadership development programs is essential for improving organizational effectiveness. This study provided valuable insights for HR management and leadership in government institutions, emphasizing the importance of integrating local cultural norms into leadership practices